Multidisciplinary approach in the study of Early Middle Age burial discovered in Sovana (GR) (Journal of Biological Research - Bollettino della Società Italiana di Biologia Sperimentale, 2012)
-
Keywords: bones; paleopathology; Tuscany; Lombard